Exclusionary Intent and Effects in the Migration Area: Interdisciplinary Reflections - Hruschka, Constantin; Rohmann, Tim; Hunkler, Christian (Quarterly on Refugee Problems - AWR Bulletin, 2022)
The increasing relevance of ‘forced‘ migration, e.g., the movements of refugees, calls for a more refined operationalisation of legal residence status and its effects on exclusion and integration. This article describes an interdisciplinary collaboration project by lawyers and sociologists to tackle this research gap. Within an inclusion-exclusion framework, different disciplinary viewpoints are developed and brought in dialogue with each other to eventually arrive at joint research questions. Starting from the observation that the continued hyperactivity of the legislator increasingly fragments residence statuses, the research project investigated the effects of legal status on the expectations and integration experiences of Afghan migrants. We reflect on the preconditions and challenges of interdisciplinary research as well as on the experiences made during the project to carve out the specifics and potentials of collaborative projects between jurisprudence and the social sciences.